Social Media as a Public Values Sphere. (4th July 2018) - Parker, Marla A.; Bozeman, Barry
Abstract : This article presents a schematic illustrating the role of social media in adjudicating public values. Such values reflect the expectations, entitlements, and civic relationships among as well as between citizens and public institutions. Such tools have become more influential in shaping civic engagement, civic identity, and political discourse—all of which reflect public values. The schematic illustrates that the advent of a current event with implicit public values will initiate several types of communication among social media users: antagonistic, critical, affirming, action-oriented, and indoctrinating. Subsequently, public values will either change, become further entrenched or new ones will emerge through coalescence, divergence, or emergence.